Anti-Roma racism and the white academic agenda: hidden blind-spots of the Education System - Fernández, Cayetano (Revista Contemporânea de Educação, 2021)
Education has been depicted as the main ‘social elevator’ to confront the internal inequalities of modern abyssal societies. Roma, as the largest, ancient European minority, are perpetually targeted as a ‘sensitive’ population in regard to access to and success in basic and higher education, creating a framework where Roma themselves, from an early age, are considered a ‘problem’. Academia, scientific research and knowledge production are not isolated from these practices and political/epistemological framework. In this sense, the article unravels its complicity and responsibility in the maintenance of the white order, the modern civilisatory mission toward the racialised bodies and the ‘ideology of integration’ as the only possible political path. This paper discusses the current academic production of evidence-based research in the field of education in regards to Roma, exploring the semantics and conceptual constructions that frame the discussion related to the Roma experience in the educative system. Furthermore, the article discusses how the conceptual codification of such a framework actually serves to condition intellectual and political approaches that attempt to go beyond the complicit ‘ideology of integration’ when addressing public and educative policies.